Therapeutic Community for Adolescents: a systematic review of the literature between 2002 and 2013 - Pedron, Camila Biribio Woerner; Buchele, Fátima (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2016)
This study is as a systematic review of scientific articles published between 2002 and 2013, and it aims to examine the publications that directly relate to the topic "therapeutic community and adolescents", indexed on predetermined databases. The articles have been arranged and classified for final analysis and through analysis carried out from bibliometric indicators. Two main subjects have been identified; the first one consists of three articles addressing the assessment and results of treatment. The second one consists of four articles and discusses aspects of the process of treatment. The studies point to positive outcomes in the care of adolescents. We identified a scarce scientific literature on the subject, especially in Brazil.